The effect of perceived stress and specialization on the relationship between perfectionism and burnout in collegiate athletes - Garinger, L. M.; Chow, G. M.; Luzzeri, M. (Anxiety, Stress and Coping, 2018)
Background: Athletic burnout is common when demands of the sport exceed the rewards. Individuals with certain personality dispositions, such as perfectionism, are at increased risk of experiencing perceived stress and subsequent burnout (Fender, L. K. (1989). Athlete burnout: Potential for research and intervention strategies. The Sport Psychologist, 3, 63-71. doi:10.1123/tsp.3.1.63; Gould, D., Tuffey, S., Udry, E., & Loehr, J. (1996). Burnout in competitive junior tennis players: I. A quantitative psychological assessment. The Sport Psychologist, 10, 322-340. doi:10.1123/tsp.10.4.322; Stoeber, J. (2011). The dual nature of perfectionism in sports: Relationships with emotion, motivation, and performance. International Review of Sport and Exercise Psychology, 4, 128-145. doi:10.1080/1750984x.2011.604789). Perfectionism has both adaptive and maladaptive dimensions, with the more maladaptive qualities leading to greater perceived stress (Hamachek, D. E. (1978). Psychodynamics of normal and neurotic perfectionism. Psychology, 15, 27-33.; Rice, K. G., & Van Arsdale, A. C. (2010). Perfectionism, perceived stress, drinking to cope, and alcohol-related problems among college students. Journal of Counseling Psychology, 57, 439-450. doi:10.1037/a0020221).